Comparative analysis of the influence of different shapes of shaft sections on dust transportation - Liu, Jie; Luo, Xuehua; Wang, Wanqing; Teng, Liangyun; Hao, Chenwei; Cai, Fei; Chen, Yi (Frontiers in Physics, 2024)
In order to study the influence of roadway section shape on dust transportation, Fluent software was used to simulate the distribution of wind flow field, dust transportation trajectory, and dust quality concentration in roadways with different section shapes. The results of the study show that, the wind speed in the roadway is in the following order from high to low: rectangle > trapezium > three-center arch > semicircular arch. Dust particles of each size rubbed each other after blasting, and there were fewer dust particles with larger sizes in the three-center arch roadway. Both the air supply distance and ventilation air volume have an effect on the dust removal effect: when the air supply distance is 5m and 10m, the three-centered arch has a better dust removal effect; when the air supply distance is 15m and 20m, it is rectangle and trapezium; and when the ventilation air volume is increased, it is three-centered arch. Through the gray correlation analysis, it can be seen that in order to improve the construction environment after blasting in the roadway, the rectangle can be chosen when considering the air supply distance, and the threecentered arch can be chosen when considering the ventilation air volume.